EDUKASI DALAM KOMUNIKASI TERHADAP KETERAMPILAN KERJA ANTAR WARGA PELAWI UTARA KECAMATAN BABALAN KABUPATEN LANGKAT - Juniarti; Harahap, Ramadhan; Novalinda (Arsil Media, 2025)
This community service activity aims to identify and understand the problems faced by the residents of Pelawi Utara Subdistrict and to formulate appropriate and applicable solutions. The main focus of the program is on strengthening interpersonal communication and developing work-related skills among community members as essential components of social and economic capital. Communication plays a strategic role in delivering accurate information and fostering harmonious social relations among residents. Meanwhile, work skills are positioned as competencies that can be enhanced to produce valuable and productive outputs. Geographically, Pelawi Utara is located in a midland area and is surrounded by other subdistricts within the Babalan District, Langkat Regency. The outcomes of the program indicate the development of more positive and active communication among residents, which is manifested through artistic works resulting from skill development activities. The impact of this initiative includes improvements in community living standards and the strengthening of social cohesion, supported by the active involvement of local government officials as facilitators and intermediaries between stakeholders.